Pattern of ABO and Rh(D) blood group among leprosy patients - Ahamad, Md Shahab Uddin; Mirjada, Md Rashed; Pahan, Dand (Journal of Chittagong Medical College Teachers' Association, 2009)
Key words: ABO blood group, Rh(D) blood group; leprosy doi: 10.3329/jcmcta.v19i2.3872 Journal of Chittagong Medical College Teachers' Association 2008: 19(2):51-53